Cataract surgery after myopic laser in situ keratomileusis: objective analysis to determine best formula and keratometry to use. Issue 4 (April 2021) - Sandoval, Helga P.; Serels, Chad; Potvin, Richard; Solomon, Kerry D.
Abstract : IOL sphere power calculations in post-LASIK eyes remain problematic. Neither total keratometry nor intraoperative aberrometry seemed to provide any significant benefit over existing formulas based on anterior keratometry. Abstract : Purpose: To objectively determine which formula/keratometry combination was best for calculating intraocular lens (IOL) sphere power in eyes with a history of myopic laser in situ keratomileusis (LASIK). Setting: One practice in the United States. Design: Retrospective, unmasked, nonrandomized chart review. Methods: Consecutive patients undergoing cataract surgery after previous myopic LASIK were included. Eyes had to have a postoperative refraction at least 3 weeks postoperatively. IOL power was calculated with the ASCRS online postrefractive IOL calculator using anterior keratometry and recalculated using total corneal power (TK). The accuracy of treatment was calculated and compared between different formulas and keratometry methods including intraoperative aberrometry (IA). Results: Data from 101 eyes, 44 of which had TK available, were analyzed. Using TK, the Wang-Koch-Maloney formula had the highest percentages of eyes with expected spherical equivalent refractive errors within 0.50 diopter (D) and 1.00 D of plano (57% and 87%, respectively). With anterior keratometry, the Barrett True-K formula had the highest percentages (64% and 92%, respectively) but was not significantly better than the Wang-Koch-Maloney formula, with expected errors within ±0.50 and ±1.00 D ( P > .2, McNemar test). Expected sphere results based on IA were not significantly different than for Barrett True-K within ±0.50 D or within ±1.00 D ( P > .2, McNemar test). Conclusions: Using TK in existing post-LASIK formulas did not seem beneficial. The formulas might have to be optimized for use with TK. The best expected results were obtained with the Barrett True-K and Haigis-L formulas using anterior keratometry. IA did not seem to materially improve results.